A Kind of Product of Submodules and Some Related Results: M. J. Nikmehr, S. Heidari, R. Nikandish - Team, Support (Thai Journal of Mathematics, 2010)
Let R be a commutative ring with identity, M an R-module and K1, K2 submodules of M. In this article, we define a kind of product between K1 and K2. In a special case of this product, we focus on M2 as an R(M)-module and we show that, in many cases, the study of M as an R-module can be replaced by the study of M2 as an R(M)-module.